Reading Images in the Religious Studies Classroom - Engler, Steven (Teaching theology and religion, 2002)
This note presents a method for teaching students to analyze and interpret images in the religious studies classroom. The technique uses two separate exercises: first analyzing images as works of art and then as conveyors of discipline-specific information. Drawing on the work of Edmund Feldman, our technique grounds interpretation in a methodical description of the basic components and characteristics of images. By helping students to conceptualize the formal qualities of an image as a first exercise, this technique allows them to more confidently address the challenging task of relating aspects of a given image with key concepts of religious studies. This simple first step toward interpreting religious images can help students profit more from texts, videos, lectures, field trips, and further studies in the field.